Examining sociodemographic risk factors for Chlamydia trachomatis infection: a population-based cohort study. (November 2017) - Somayaji, Ranjani; Naugler, Christopher; Guo, Maggie; Church, Deirdre L
Aim: Chlamydia trachomatis is the most prevalent bacterial sexually transmitted infection in developed nations and is an important public health concern. We aimed to assess the factors associated with testing and positivity of C. trachomatis in a large population.Methods: A retrospective study of a large Canadian health region was undertaken using 2011 census and laboratory data. Demographic and socioeconomic data from the national household survey were linked to microbiologic data for C. trachomatis . Multivariable generalized estimating equation models were constructed to examine relative risk for C. trachomatis testing and positivity.Results: For testing and positivity, female sex and younger age groups were associated with increased risk. University education and South Asian ethnicity were associated with lower risk of positivity.Conclusion: Incorporating socio-demographic factors will be critical to the success of future sexually transmitted infection public health programs.